The Impact of Gender Inclusion on Economic Development in Emerging Economies - Abbas, Syed Tahir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper examines the impact of gender inclusion on the economic development of emerging economies. By integrating gender perspectives into the developmental strategies, not only do societies become more equitable, but their economic growth is also significantly enhanced. The research adopts a multi-faceted approach that includes a comprehensive literature review, in-depth case studies, empirical research, and detailed policy analysis to investigate the relationship between gender-inclusive policies and economic performance. The findings underscore the critical role of gender equality in driving economic success in emerging economies, suggesting that gender inclusion is not merely a societal goal but a cornerstone of sustainable economic strategy. This study provides valuable insights for policymakers, stakeholders, and researchers interested in leveraging gender inclusivity to boost economic development and achieve broader social outcomes.